Anatomi berorientasi klinis : Edisi kelima, Jilid 2 / Keith L. Moore dan Arthur F. Dalley; Penerjemah, Huriawati Hartanto - MOORE, Keith L.; DALLEY, Arthur F.; HURIAWATI Hartanto (Erlangga, 2013)
xix, 402 hlm. : ilus. ; 28,5 cm.